Zmienność genetyczna jodły pospolitej (Abies alba Mill.) zachowanej na terenie Nadleśnictwa Katowice - Masternak, Katarzyna; Głębocka, Katarzyna; Niebrzydowska, Barbara (Leśne Prace Badawcze, 2015)
Environmental pollution greatly decreases a tree’s health and results in dieback of forest stands. Due to increasing industrial activity in the 20th century, silver fir became almost totally extinct in the Katowice Forest District. Only 19 individuals have survived to this day. The aim of the present study was to analyze growth characteristics and polymorphisms of 25 inter-simple sequence repeats (ISSR) of the preserved trees. The mean height of the inventoried silver firs was 19 m with a diameter at breast height (DBH) of 29 cm. Flowers were observed on few trees only. However, all trees were of high vitality without signs of fungal pathogen infections or insect outbreaks. Parameters of genetic variability, including mean effective number of alleles per locus and expected heterozygosity, were higher than described in the literature so far and they amounted to 1,659, 0,396 respectively.